2002
DOI: 10.1021/jo025793h
|View full text |Cite
|
Sign up to set email alerts
|

First Stereoselective Synthesis of 2-Deoxy-α-d-ribosyl-1-phosphate:  Novel Application of Crystallization-Induced Asymmetric Transformation

Abstract: A first stereoselective synthesis of bis(cyclohexylamine) 2-deoxy-alpha-D-ribosyl-1-phosphate has been achieved. The synthesis features a key crystallization-induced asymmetric transformation (AT) to generate a desired alpha-anomer in 99% yield at a 98.8:1.2 ratio of alpha/beta.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…First of all, they have developed “crystallization–induced asymmetric transformation” for the stereoselective synthesis of 2–deoxy– α – D –ribofuranose–1–phosphate ( 48 ) and its β – D –anomer [125, 126]. Both anomers have been isolated as pure stable bis(cyclohexylammonium) salts.…”
Section: New Trends In Biotechnology Of Nucleosidesmentioning
confidence: 99%
“…First of all, they have developed “crystallization–induced asymmetric transformation” for the stereoselective synthesis of 2–deoxy– α – D –ribofuranose–1–phosphate ( 48 ) and its β – D –anomer [125, 126]. Both anomers have been isolated as pure stable bis(cyclohexylammonium) salts.…”
Section: New Trends In Biotechnology Of Nucleosidesmentioning
confidence: 99%
“…Similarly, reaction of 11 with either K 3 PO 4 or Na 3 PO 4 failed to lead to the desired OMP product. We were finally able to successfully substitute 11 by following the example of Komatsu and co‐workers, who found that a tri( n ‐butyl)amine salt of phosphate could be successfully reacted with a chloroalkyl ether, presumably because of its improved solubility in organic solvents 26. 27 Thus, stirring 11 with a tri( n ‐butyl)amine salt of phosphate in acetonitrile led to 12 , which was then deprotected using hydrogen and Pd/C in methanol.…”
Section: Resultsmentioning
confidence: 99%
“…e l s e v i e r . c o m / l o c a t e / t e t a s y process via crystal-induced asymmetric transformation (CIAT) [26][27][28][29][30][31][32][33][34][35][36][37][38] in a mixed solvent of toluene and nitromethane afforded cis-4a-HCl in 93% yield and with 98% de. However, high trans-stereoselectivity rather than cis-stereoselectivity is required to satisfy the absolute configurations of the two stereogenic centers of the title compounds HR22C16 and its analogues.…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%